A situational Analysis of the faculties’ Industrial Attachment programme at public Technical Training Institutes (TTIs) in Bhutan - Tshewang, Sangay (International Journal of Humanities and Education Development (IJHED), 2021)
The study was conducted in three Technical Training Institutes (TTIs) in Bhutan. The objective of the study was to investigate the challenges facing industrial attachment as a learning experience for automobile faculties. The population of the study involved all the faculties of TTIs namely Ranjung, Thimphu and Samthang. However, the researcher used a sample size of 64 respondents (purposive sampling) for the study. The data was collected from the respondents through a research-designed survey questionnaire administered through the Online Google Form. Nonetheless, 58 questionnaires were received. The validity and reliability of the instruments were determined by pre-testing the instruments before taking into consideration for analysis. The data collected was analysed using SPSS software. Cronbach‐Alpha analysis was used to determine the reliability value of data. And the value of pre-test data was calculated at 0.788. The findings of the study concluded that the faculties of the three automobile institutes expressed high satisfaction with the program objectives, the usefulness of the program, adequacy of knowledge and skills acquired through the program. However, the study also concluded that the challenges they faced compromised the quality of engagement and meaningful learning experience. In this context, the researcher recommended that industrial attachment must be planned and implemented as a genuine learning experience right from the start. This could be done by allocating adequate funds to support the faculties' interns and, enable the Technical Vocational Education and Training (TVET) institution to maintain the relevancy of the attachment program and the industry. The immediate attachment supervisors of the industries should also be trained to deliver quality training and education to the faculties during the industrial attachment. This calls for a closer and synergized working relationship between the TVET institutions and the industries so that effective and uncompromised industrial attachment is ensured